MMDAE: Dialog scenario editor for MMDAgent on the web browser - Nishimura, Ryota; Yamamoto, Daisuke; Uchiya, Takahiro; Takumi, Ichi (ICT express, 2019)
We have developed MMDAgent (a fully open-source toolkit for voice interaction systems), which runs on a variety of platforms such as personal computers and smartphones. From this, the editing environment of the dialog scenario also needs to be operated on various platforms. So, we develop a scenario editor that is implemented on a Web browser. The purpose of this paper also includes making it easy to edit the scenario. Experiments were conducted for subjects using the proposed scenario editor. It was found that our proposed system provides better readability of a scenario and allows easier editing. Keywords: Spoken dialog system, Scenario editor, Web browser, MMDAgent